Occupational risk factors among Iranian farmworkers: a review of the available evidence - Mahin Ghafari; Zahra Cheraghi; Amin Doosti-Irani (Epidemiology and Health, 2017)
Farming is one of the most important components of most economies. No comprehensive picture exists of the health status of Iranian farmers and the work-related hazards that affect them. We aimed to determine the gaps in the current knowledge regarding the occupational health of Iranian farmworkers. Electronic databases including Medline, Web of Science, Scopus, and Embase, as well as national databases including the Scientific Information Database, MagIran, and Barakat Knowledge System, were searched for articles published through March 2017. All epidemiologic studies regarding the occupational health of farmworkers in Iran were reviewed, regardless of their design, language, time of publication, and location. Of the 86 retrieved articles, 39 studies were ultimately analyzed. Most studies were conducted in Fars, Kerman, and Mazandaran provinces. According to the results of this review, chemical, physical, and biological hazards, along with work-related injuries, may be the main factors threatening the health of farmworkers. The unsafe use of pesticides was related to male infertility, eye and digestive complications, pesticide poisoning, pesticide absorption, hematological changes, non-Hodgkin lymphoma, and multiple myeloma. Chemical hazards (e.g., the unsafe use of pesticides), physical hazards, injuries, and biological hazards (e.g., work-related infectious diseases) threaten the health of Iranian farmworkers. Moreover, farmworkers lack adequate knowledge about the occupational hazards they face and the relevant risk factors.